A longitudinal analysis of sugar-sweetened beverage intake in infancy and obesity at 6 years - Pan, Liping; Li, Ruowei; Park, Sohyun; Galuska, Deborah A; Sherry, Bettylou; Freedman, David S (Pediatrics (Evanston), 2014)
To examine whether sugar-sweetened beverage (SSB) intake during infancy predicts obesity at age 6 years. We included 1189 children who participated in the Infant Feeding Practices Study II in 2005-2007 and were followed up at 6 years in 2012. Children's weight and height were measured by mothers. Obesity was defined as gender-specific BMI-for-age ≥95th percentile. We used logistic regression to estimate the associations of any SSB intake and age at SSB introduction before 12 months and mean SSB intake during ages 10 to 12 months with obesity at 6 years controlling for baseline characteristics. The obesity prevalence at 6 years among children who consumed SSBs during infancy was twice as high as that among non-SSB consumers (17.0% vs 8.6%). The adjusted odds of obesity at 6 years was 71% higher for any SSB intake and 92% higher for SSB introduction before 6 months compared with no SSB intake during infancy. Children who consumed SSBs ≥3 times per week during ages 10 to 12 months had twice the odds of obesity compared with those who consumed no SSBs in this period. However, among children who consumed SSBs, the odds of obesity at 6 years did not differ by age at SSB introduction during infancy or by mean weekly SSB intake during ages 10 to 12 months. Children who consumed SSBs during infancy had higher odds of obesity at 6 years than non-SSB consumers. SSB consumption during infancy may be a risk factor for obesity in early childhood. Whether unmeasured behaviors contributed to the association is unclear.